The Persian Version of the Nottingham Leisure Questionnaire: Translation, Cultural Adaptation, and Psychometric Properties - Majid Farhadian; Mitra Khalafbeigi; Malahat Akbarfahimi; Peyman Abharian; Farzaneh Yazdani; Ali Shoaei (Shiraz University of Medical Sciences, 2024)
Background: Leisure as an occupation plays an important role in people's daily lives. This study aimed to translate and culturally adapt the original Nottingham Leisure Questionnaire to Persian and assess the psychometric properties of the Persian version.Method: One hundred and forty healthy individuals participated in this cross-sectional study. Face and content validity were assessed by determining the impact score of the item, content validity ratio, and content validity index methods. Convergent validity was assessed using the correlation method between the Nottingham Leisure Questionnaire and the Occupational Balance Questionnaire-11, Meaningful Activity Participation Assessment, 36-item short-form health survey, and Satisfaction with Life Scale. The reliability of the Persian version of the Nottingham Leisure Questionnaire was assessed by internal consistency and test-retest reliability. Data analysis was conducted using SPSS. v. 23.0 software at a significance level of 0.05.Results: Face and content validity demonstrated an acceptable range (impact score: 2.2 to 4, content validity ratio: 0.57 to 1, and content validity index: 0.87 to 1). Significant correlations between assessment tools supported Convergent Validity. There was moderate internal consistency (α = 0.77) and excellent test-retest reliability for the number of leisure scores (interclass correlation coefficient [ICC] = 0.894) and frequency of leisure participation scores (ICC = 0.883).Conclusions: The Persian version of the Nottingham Leisure Questionnaire is a psychometrically valid, reliable, and useful instrument to assess leisure in healthy Persian-speaking participants.